1991
DOI: 10.1111/j.1469-8137.1991.tb00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the ovular structures in peach [Prunus persica (L.) Batsch]

Abstract: SUMMARYChanges in the ovular tissues of peach (Prunus persica (L.) Batsch) were studied from anthesis to fertilization or degeneration in pollinated and unpolHnated flowers. During this time the ovule undergoes a continuous developmental process. At anthesis the megagametophyte is immature and is not fully developed until 12 days later. Durmg the first three weeks following anthesis the ovule increases in length from 400 to 1200/fm, and the nucellus and integuments undergo various changes particularly in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 44 publications
4
42
0
4
Order By: Relevance
“…In line with observations of Cerović andMićić (1999) in C. avium andArbeloa andHerrero (1991) in P. persica, we found antipode degeneration before fertilization. These authors observed antipode degeneration 3 days after they developed.…”
Section: Discussionsupporting
confidence: 92%
“…In line with observations of Cerović andMićić (1999) in C. avium andArbeloa andHerrero (1991) in P. persica, we found antipode degeneration before fertilization. These authors observed antipode degeneration 3 days after they developed.…”
Section: Discussionsupporting
confidence: 92%
“…B (2003) clear. Indeed, in some species such as in the peach (Arbeloa & Herrero 1991), the female gametophyte does not even exist at the time when the sporophytic machinery necessary for fertilization is established. There is little information on the lifespan of the megagametophyte, but observations on Prunus species (M. Herrero, unpublished results) show that it is surprisingly short.…”
Section: Perspectivesmentioning
confidence: 99%
“…As reservas de amido desempenham um importante papel no processo reprodutivo (HERRERO; HORMANZA, 1996), pois influenciam no desenvolvimento das estruturas ovulares e no desenvolvimento do embrião (ARBELOA; HERRERO, 1991).…”
Section: Methodsunclassified